2023
DOI: 10.1097/aln.0000000000004856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Individualized Lung Protective Ventilation on Lung Strain and Stress in Children Undergoing Laparoscopy: An Observational Cohort Study

Cecilia M. Acosta,
Sergio Poliotto,
Diego Abrego
et al.

Abstract: Background Exaggerated lung strain and stress could damage lungs in anesthetized children. We hypothesized that the association of capnoperitoneum and lung collapse in anesthetized children increases lung strain-stress. Our primary aim was to describe the impact of capnoperitoneum on lung strain-stress and the effects of an individualized protective ventilation during laparoscopic surgery in children. Methods We performed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a previous clinical study, EELVCO 2 showed excellent trending ability with concordance rates of 100% with the reference methods [ 10 ]. In two more recent studies the method demonstrated a good performance helping to select a protective level of PEEP in adult patients [ 11 ] and children [ 12 ] submitted to laparoscopic surgery.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…In a previous clinical study, EELVCO 2 showed excellent trending ability with concordance rates of 100% with the reference methods [ 10 ]. In two more recent studies the method demonstrated a good performance helping to select a protective level of PEEP in adult patients [ 11 ] and children [ 12 ] submitted to laparoscopic surgery.…”
Section: Clinical Relevancementioning
confidence: 99%
“…A salient feature of this method is its ability to measure EELV on a breath-by-breath basis being the first method providing continuous absolute EELV values. The potential advantages of this feature have already been advanced in recent evaluations assessing its ability to characterize the lung and adjust the level of end-expiratory positive pressure (PEEP) during laparoscopic surgery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%